The Utilization of Instagram Social Media To Improve Students’ Skill In Writing Descriptive Text - Dewi Muliasari (International Journal of Seocology, 2020)
The aims of this research is knowing the use of Instagram social media and knowing the improvement of writing skills of seventh grade students of SMP N 1 Semin. This type of research uses classroom action research. The research method used is quantitative descriptive to analyse data using numbers. The subjects in this research were students of class VIIA SMP 1 Semin. The number of students was 20 children, while the object in this research was the process (implementation of the description text in teaching learning process with the help of social media namely Instagram in class VIIA SMP 1 Semin and the results (in the form of scores obtained by students during learning activities to write descriptive text skills with the help of social media Instagram). The results shows that all students, especially class VIIA SMP 1 Semin know the social media Instagram. Most of the students are active users of Instagram. Instagram media is not used properly or is not used for any of the media when they are studying. For pre-action results in skills write a description of the average score of students 55.5. In the first cycle the average value of 68 increased by 12.5, while in the second cycle the average value of 75.25 increased from the first cycle of 7.25.